Protocol for the dissection, immunostaining, and imaging of whole-mount mouse choroid plexus - Lillian I.J. Byer; Huixin Xu; Maria K. Lehtinen (STAR Protocols)
Summary: Extracting the choroid plexus (ChP) for histology provides a comprehensive view of the whole tissue and is crucial for understanding its structure and cellular interactions. Here, we present a protocol for dissecting out the lateral, third, and fourth ventricle ChP from mice and the immunostaining process. We also detail procedures for preparing whole-mount ChP tissue and imaging techniques, such as tile scan and Z-stacks.For complete details on the use and execution of this protocol, please refer to Xu et al.1 : Publisher’s note: Undertaking any experimental protocol requires adherence to local institutional guidelines for laboratory safety and ethics.